OPTIMALISASI BIAYA PENGIRIMAN PAKET MENGGUNAKAN METODE LEAST COST DAN LINGO PADA PT. SICEPAT EKSPRES INDONESIA - Dikdik Rinaldi; Nur Aditio Pribadi; Muhammad Fadhil; Muchammad Fauzi (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2021)
Transportation is a very important means in supporting the success of the delivery of a good. In almost all expedition service companies, transportation acts as the spearhead in the company's success because it can be one of the factors of consumer satisfaction. Transportation problems occur a lot in the distribution of goods that are not appropriate, so the cost of shipping can be very high. By using the transportation model, shipping costs can be optimized and distribution lines will be more precise. The research method is used to solve various problems that occur by using Least Cost by evaluating stepping stone methods and proving using Lingo